1885 Wis. Sess. Laws 753, ch. 159, § 3, pt. 44 - (:unkn) unknown (My University, 1885)
Authorized the city to regulate and prohibit the carrying concealed of any pistol, sling shot, knuckles, Bowie knife, dirk knife, dirk, dagger, or any other dangerous or deadly weapon.
Keywords: CARRY - CONCEALED